1999
DOI: 10.1093/emboj/18.8.2066
|View full text |Cite
|
Sign up to set email alerts
|

AUX1 regulates root gravitropism in Arabidopsis by facilitating auxin uptake within root apical tissues

Abstract: Plants employ a specialized transport system composed of separate influx and efflux carriers to mobilize the plant hormone auxin between its site(s) of synthesis and action. Mutations within the permease-like AUX1 protein significantly reduce the rate of carrier-mediated auxin uptake within Arabidopsis roots, conferring an agravitropic phenotype. We are able to bypass the defect within auxin uptake and restore the gravitropic root phenotype of aux1 by growing mutant seedlings in the presence of the membrane-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
458
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 545 publications
(484 citation statements)
references
References 43 publications
24
458
0
2
Order By: Relevance
“…Experiments with auxin transport inhibitors in Arabidopsis have demonstrated that the auxin movement from the shoot toward the root tip is responsible for lateral root development (Reed et al, 1998), while auxin movement away from the root tip is required for gravitropism and primary root elongation (Rashotte et al, 2000), although involvement of basipetal auxin transport in lateral root formation has also been discussed recently (Casimiro et al, 2001). Several genes involved in auxin transport, including the postulated efflux carriers of the pin family (Gälweiler et al, 1998;Mü ller et al, 1998;Friml et al, 2002aFriml et al, , 2002b, the auxin importer aux1 (Marchant et al, 1999), and the postulated efflux carriers pgp1, pgp2, and pgp19 (Noh et al, 2001), have been cloned recently in Arabidopsis. The maize ortholog of pgp1 is not expressed in roots (Multani et al, 2003).…”
mentioning
confidence: 99%
“…Experiments with auxin transport inhibitors in Arabidopsis have demonstrated that the auxin movement from the shoot toward the root tip is responsible for lateral root development (Reed et al, 1998), while auxin movement away from the root tip is required for gravitropism and primary root elongation (Rashotte et al, 2000), although involvement of basipetal auxin transport in lateral root formation has also been discussed recently (Casimiro et al, 2001). Several genes involved in auxin transport, including the postulated efflux carriers of the pin family (Gälweiler et al, 1998;Mü ller et al, 1998;Friml et al, 2002aFriml et al, , 2002b, the auxin importer aux1 (Marchant et al, 1999), and the postulated efflux carriers pgp1, pgp2, and pgp19 (Noh et al, 2001), have been cloned recently in Arabidopsis. The maize ortholog of pgp1 is not expressed in roots (Multani et al, 2003).…”
mentioning
confidence: 99%
“…It was reported that under high salt, the inhibition of lateral root formation is caused by suppression of basipetal auxin transport, resulting in over-accumulation of auxin in root epidermis of elongation zone while depleting auxin in root apex (Wang et al 2009). AUX1 encodes a non-redundant auxin influx carrier (Marchant 1999), which facilitates auxin distribution in lateral root cap and elongation of epidermal cells (Marchant et al 2002; Band et al 2014). The aux1-7 mutant exhibited higher susceptibility to salt stress than the wild type, suggesting that auxin transport is required for alleviating salt stress (Wang et al 2009; Galvan-Ampudia and Testerink 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The influx of dissociated auxin anion (IAA -) together with 2H + from apoplast to cytoplasm is mediated by a family of amino acid permease-like proton-gradientdriven transporter proteins, AUX1//LAX, located in an anti-polar side of plasma membrane, whereas partially IAA also moves passively via lipophilic diffusion (Bennette et al, 1996;Marchant et al, 1999;Swarup et al, 2001). Thus, AUX1 is possible to be involved in both regulation of gravitropism in roots and auxin influx as carrier proteins.…”
Section: Mechanisms Of Auxin Polar Transport: Chemiosmotic Modelmentioning
confidence: 99%